Institutional Reactions to the Impact of Global Crisis at Source and Destination Cities of Migration in China - Mária Csanádi (Hungarian Academy of Sciences, Institute of Economics, 2010)
This paper relates on the impact of global crisis on China from a systemic point of view. In what ways external and internal adaptation pressures influenced the transformation of the party-state system in China? Did reactions have an impact on the transformation of political or economic system? The purpose of our small field research was to respond to this question by examining institutional reactions to crisis from late 2008 to late 2009. We have examined the common and disparate characteristics of institutional adaptation at prefecture level at sources and destination cities of migration. We have also tried to detect their common or different sensitivity to crisis analyzing the periods before, during and after the crisis. We shall reflect on the reasons of prevailing political stability despite sudden large unemployment, and substantial economic, social and political impact on the party-state system. The paper uses interviews in 13 prefectures and newspaper analysis of 16 prefectures from mid 2008 to the end of 2009 complemented by available relevant statistical data.
Keywords: F5; D78; R58; J08; O15; E24; 330; system transformation; global crisis; migration; economic policy reactions; prefectures; Systemtransformation; Institutioneller Wandel; Wirtschaftskrise; Finanzkrise; Binnenwanderung; Wirtschaftspolitik; China